Building tomorrow: additive manufacturing unleashing sustainable progress in the US military - Daniela-Elena Hrab; Gheorghe Minculete (Insights into Regional Development)
Additive manufacturing (AM) has recently attracted the attention of academia and private companies, viewing it as a tool for achieving sustainability within the context of sustainable development (SD). As the previous studies revealed an ongoing debate on the sustainable nature of AM, making it challenging to conclude, the primary objective of this article is to explore new perspectives that enhance the contribution of AM to the sustainability vision. Given the limited number of studies considering the potential contribution of AM to specific Sustainable Development Goals (SDGs) and associated targets, this research aims to complete the existing body of knowledge through an in-depth analysis. Furthermore, recognizing that AM could generate some unsustainable effects from a security standpoint, this study investigates how the military organization, with its capacity to mitigate such concerns, could contribute to implementing specific SDGs and targets through AM small and large-scale adoption. Therefore, the study follows a qualitative approach, studying the case of the American military forces in an attempt to reveal the main reasons for adopting AM and the possible contribution to specific SDGs and targets. The results highlight a consistent potential for the US military to contribute to SD, mainly through the large-scale adoption of AM. This measure could reduce their military logistic footprint and provide financial, operational and strategic advantages. While the main findings are presented in a detailed list which supports these conclusions and offers valuable lessons learned, it is essential to acknowledge the limitations of this research – namely, the lack of quantitative evidence. Therefore, to formulate a conclusive judgment on the sustainable nature of AM, future studies should concentrate on assessing financial data from private and public entities, including military organizations.